Pemanfaatan Media Sosial Instagram sebagai Media Penyampaian Informasi dan Promosi di Coffe Shop House Of Musi - Stefi Ananta Rivelia; Marlini Marlini; Rini Asmara (KAMPUS AKADEMIK PUBLISING, 2026)
The development of social media has encouraged business owners to utilize it as a medium for information dissemination and promotion, particularly in the culinary sector such as coffee shops. Instagram is one of the most widely used social media platforms due to its visual and interactive features. This study aims to analyze the use of Instagram as a medium for information delivery and promotion at House of Musi Coffee Shop. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation, and documentation. The research informants consisted of the coffee shop owner, Instagram social media administrator, and customers of House of Musi. The results indicate that Instagram is actively used to deliver information related to menus, promotions, operating hours, and music events, as well as to promote the coffee shop and attract customer visits. Visually appealing content, the use of Instagram features such as stories and reels, and active interaction with customers are key factors in promotional effectiveness. However, challenges such as limited resources and changes in Instagram’s algorithm were also identified. Overall, Instagram is proven to be an effective medium for information dissemination and promotion for House of Musi Coffee Shop when managed consistently and creatively.